Effects of Malting and Fermentation on Anti-Nutrient Reduction and Protein Digestibility of Red Sorghum, White Sorghum and Pearl Millet - Onyango, C. A.; Ochanda, S. O.; Mwasaru, M. A.; Ochieng, J. K.; Mathooko, Francis M.; Kinyuru, J. N. (My University, 2013)
Sorghum and millet and their products require specialized treatment in order to improve their nutritive value, organoleptic properties and shelf-life. They contain anti-nutrients which are the major phytochemicals which negatively affects their nutritive values. The phytochemicals of concern include tannins and phytates, which interfere with mineral absorption, palatability and protein digestibility. Malting and fermentation treatments were applied to reduce the anti-nutrients, improve protein digestibility, and acidity to increase the products shelf life. The effects of malting and fermentation on the cereals nutritive value and anti-nutrient reduction were studied and evaluated for a period of 8 days. A treatment combining malting for 3 days and fermentation for 2 days respectively both at room temperatures (25°C) was employed. Tannins and phytates were significantly reduced (p ? 0.05) by malting and fermentation. Protein digestibility was significantly (p ? 0.05) improved by malting and fermentation treatments; malted cereals digestibility ranged between 34.5-68.1% while the fermented flours protein digestibility range was 97.4-98.3%. The pH values were lowered to below 4.0, a level at which they could effectively inhibit spoilage microorganisms at the end of the fermentation period. A combination of optimum time treatments of malting and fermentation for 3 days and 2 days respectively were effective in reducing tannins and phytates and improving protein digestibility of the cereals.